University Social Responsibility, University Image And Hight Education Performance - Sunardi Sunardi (Indonesian Management and Accounting Research, 2019)
The purpose of the study was to test empirically the direct and indirect influence of university social responsibility, university image and hight education performance. Data used primary data, using questionnaire instrument with total  respondents 138 people consisting of leaders of private universities (11 universities and 48 faculties), sample determination used purposive sampling technique, after validity and reliability test, the number of statements processed as many as 38 items. Furthermore, data processing was using Structural Equation Model with partial least square approach (PLS). The findings result showed that university social responsibility had positive and significant impact to the image of university, while university social responsibility influenced positively and insignificant to the height education performance, university image also had a positive and significant impact on the hight education performance. The limitations of this study did not consider the variable number of students, the total assets owned by the university and the ownership status of the university. The research results had implications in the preparation of university work program and budgeting process, as well as the university promotion tool.